The Dynamics of a Hybrid Chaotic System - Ramos, Carlos (2020)
We consider a forced damped piecewise linear oscillator whose motion is modeled by the second-order non-autonomous differential equation. Our hybrid chaotic system has a continuous regime, where the time flow is characterized by the explicit solutions of the ordinary differential equations, and a singular regime, where the time flow is characterized by an appropriate transformation linking the explicit solutions from one domain to the other. The purpose of this work is to study the complex behaviour of the system, namely the dependence on initial conditions and parameter variation.